A Contribution to the History of the National Union of Public Employees: A View from Cumbria, 1969–1979. Issue 39 (September 2018) - Rowbottom, David S.
Abstract : The National Union of Public Employees (NUPE) gained public prominence in the 1970s through its campaigns for low-paid workers in the public sector. Stephen Williams and Bob Fryer's Leadership and Democracy, the second volume of the history of NUPE (1928–1993), is described by the authors as a 'top-down national history', but rarely goes very far 'down'. Dave Lyddon in his review essay (HSIR 38) provides his own commentary, including the roles of women in the union and that of appointed full-time officers. This comment, by an appointed full-time officer, fills some gaps in the history of NUPE provided by the above authors by examining activities at a local level. It covers: innovations in recruiting and retaining members; how the introduction of bonus schemes helped promote the appointment of union stewards; the impact of the reorganization of local government and the National Health Service in 1974; and a comparison of the responses of members to industrial action in the early part of the 1970s and in the 'Winter of Discontent' of 1979.